Compost ingredient and its use in crop cultivation. - Ahmed, Osumanu Haruna; Petrus Rudut, Auldry Chaddy; Ab. Majid, Nik Muhammad (2010)

(untitled)
The present invention discloses a compost for cultivating crops, the compost including fibres and water, the use of such compost in crop cultivation and methods of cultivating crops using the fibres and water. The fibres and water are by-products derived from sago palms in the production starch.